2011
DOI: 10.1111/j.1365-2133.2011.10211.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiling of stratum corneum biophysical and molecular properties

Abstract: The techniques used in this study provide rapid noninvasive measures of the spatial distribution of corneocyte maturity and surface area as well as protease activity and protein content within different levels of the stratum corneum layers. The methods used will allow mechanistic insight into the effects of formulation excipients and active ingredients on epidermal turnover and skin barrier function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 56 publications
5
44
0
Order By: Relevance
“…The same 37 individuals were assessed for plasmin, C‐1 and BH activities. Protease activities were determined on the fifth tape stripping using previously reported methods …”
Section: Methodsmentioning
confidence: 99%
“…The same 37 individuals were assessed for plasmin, C‐1 and BH activities. Protease activities were determined on the fifth tape stripping using previously reported methods …”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the protein content, which was measured for each individual tape strip. As noted previously 10 the amount of protein removed decreased was more SC was removed, reflecting increased cohesion of the deeper layers 14–16 …”
Section: Resultsmentioning
confidence: 62%
“…Stratum corneum samples were obtained by tape stripping as described above. Protease activity was measured for tape strip numbers 2–4, 6–8, 10–12, 14–16 and 18–20 as previously described 10 …”
Section: Methodsmentioning
confidence: 99%
“…Mohammed et al found similar results [ 144 ] ; moreover, they report decreased corneocyte maturity and surface area with increasing number of tape strippings similar to Hirao [ 145 ] and Harding et al [ 146 ] .…”
Section: Rate Of Desquamationmentioning
confidence: 51%